The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1021/acsaem.2c02547
|View full text |Cite
|
Sign up to set email alerts
|

Constructing a Two-Dimensional SnWO4 Nanosheet Array Film for Enhanced Photoelectrochemical Performance

Abstract: Stannous tungstate (α-SnWO4) is a promising photoanode material for photoelectrochemical (PEC) water splitting, but its practical performance is severely limited by the charge recombination problem that results from poor bulk charge transport ability. Herein, SnWO4 with a two-dimensional (2D) sheet-like array morphology (SnWO4-NS) was formed to provide pathways for accelerating charge transport, which is demonstrated by the small radius of electrochemical impedance spectroscopy and a short charge transport tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…The addition of fluoride ions in a hydrothermal process was used to fabricate 2D sheet-like arrays of SnWO 4 , which improved the photocurrent density from 0.086 to 0.41 mA cm −2 . 297 The reason for the improvement of optoelectronic performance is that the morphology of the 2D sheet array provides a high-speed movement path for the migration of carriers. The hydrothermal F − added SnWO 4 film was annealed in argon at 500°C to obtain a long sheet-like SnWO 4 film, which exhibited a photocurrent density of 0.79 mA cm −2 at 1.23 V versus RHE in the absence of any sacrificial agent.…”
Section: Awomentioning
confidence: 99%
See 1 more Smart Citation
“…The addition of fluoride ions in a hydrothermal process was used to fabricate 2D sheet-like arrays of SnWO 4 , which improved the photocurrent density from 0.086 to 0.41 mA cm −2 . 297 The reason for the improvement of optoelectronic performance is that the morphology of the 2D sheet array provides a high-speed movement path for the migration of carriers. The hydrothermal F − added SnWO 4 film was annealed in argon at 500°C to obtain a long sheet-like SnWO 4 film, which exhibited a photocurrent density of 0.79 mA cm −2 at 1.23 V versus RHE in the absence of any sacrificial agent.…”
Section: Awomentioning
confidence: 99%
“…In addition to the size of nanoparticles affecting the carrier transport performance, the nanostructure affects the carrier transport performance. The addition of fluoride ions in a hydrothermal process was used to fabricate 2D sheet‐like arrays of SnWO 4 , which improved the photocurrent density from 0.086 to 0.41 mA cm −2 297 . The reason for the improvement of optoelectronic performance is that the morphology of the 2D sheet array provides a high‐speed movement path for the migration of carriers.…”
Section: Recent Developments Of Abo4 Photoanode Materialsmentioning
confidence: 99%
“…This method was further improved by several researchers, including He et al [55][56][57] They synthesized nanostructured α-SnWO 4 thin films on fluorine-doped tin oxide (FTO) substrates using approximately the same method as described by Pyper et al, but with the addition of a post-annealing process conducted at 500 °C under an Ar atmosphere. 57 It was argued that the annealing step under an inert atmosphere would influence the oxidation state of α-SnWO 4 , preventing the formation of Sn 4+ . As a result, as shown in Fig.…”
Section: Conversion From Womentioning
confidence: 99%
“…The material shows n-type conductivity, which means that it should be employed as the photoanode in PEC water splitting devices. Several studies have been reported in the last few years on α-SnWO 4 films prepared by different techniques, [10][11][12][13][14][15][16][17][18][19][20][21][22] e.g., hydrothermal synthesis, reactive magnetron sputtering, pulsed laser deposition, and chemical vapor deposition. The attractive properties of this material as a photoanode include the bandgap of 1.9 eV, which is close to ideal for use as a top absorber in a tandem configuration, and the favorably low onset potential of %0 V versus RHE.…”
Section: Introductionmentioning
confidence: 99%
“…[18,25] Epitaxial or highly oriented films are therefore expected to have much improved charge transport, and indeed recent reports on two-dimensional α-SnWO 4 crystalline nanosheets with preferred {001} orientation demonstrated superior performance. [18][19][20] Another limitation is the modest photovoltage that can be extracted from the material, despite the fact that the band positions straddle the water reduction and oxidation potentials (which would enable a maximum quasi-Fermi level splitting of at least 1.23 V under operating conditions). In our earlier study on NiO x -coated α-SnWO 4 , in which the NiO x serves as the protection layer, we showed that the limitation of the photovoltage can be correlated with the formation of an interfacial oxide layer at the interface of α-SnWO 4 and NiO x .…”
Section: Introductionmentioning
confidence: 99%